2015
DOI: 10.1021/acs.est.5b00648
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Neat Biodiesel and Biodiesel and HVO Blends in Diesel Fuel on Exhaust Emissions from a Light Duty Vehicle with a Diesel Engine

Abstract: The influence of fatty acid methyl esters (FAME) and hydrotreated vegetable oil (HVO) diesel blends on the exhaust emissions from a passenger car was examined. The impact of FAME for the cold urban phase (UDC) was increased CO and HC emissions, probably due to blend physical properties promoting incomplete combustion. The HVO blend caused the lowest CO and HC emissions for the UDC. NOx emissions did not change significantly with the fuel used, however the UDC was characterized by lower NOx emission for FAME bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 50 publications
3
25
0
Order By: Relevance
“…Reduced BC emissions have been found in several previous studies [56][57][58]. Other studies have found a slight increase in total PAH concentration for blends with HVO compared to other types of biodiesel [59] even though the HVO fuel is free of aromatics. We hypothesize that this can be attributed to its homogeneous composition and few large compounds associated with high vaporization enthalpies.…”
Section: Organic Aerosol and Pah Emissionsmentioning
confidence: 62%
“…Reduced BC emissions have been found in several previous studies [56][57][58]. Other studies have found a slight increase in total PAH concentration for blends with HVO compared to other types of biodiesel [59] even though the HVO fuel is free of aromatics. We hypothesize that this can be attributed to its homogeneous composition and few large compounds associated with high vaporization enthalpies.…”
Section: Organic Aerosol and Pah Emissionsmentioning
confidence: 62%
“…Several other studies have provided detailed emission profiles of VOCs, carbonyl compounds, and polycyclic aromatic hydrocarbons (PAHs), with the majority of these studies not reaching a consensus on the impact of biodiesel due to conflicting trends (George et al, 2014;Prokopowicz et al, 2015;Rouce et al, 2012). Magara-Gomez et al (2012) found decreases in toluene, ethylbenzene, m/p-xylenes, o-…”
Section: Introductionmentioning
confidence: 99%
“…To reduce carbon emissions and their effects on global warming and ocean acidification, conversion of marine vessels to fuels derived from renewable (plant-based) sources could be a reasonable alternative to fossil fuelbased diesels, such as ultra-low sulfur diesel or ULSD. Hydrotreating of vegetable oil has been shown to produce a renewable biodiesel (hydrogenation-derived renewable diesel or HDRD; also referred to as hydrogenated vegetable oil or HVO) that is more compatible with many existing diesel engines than other untreated biofuels (Aatola et al 2008;Heikkil€ a et al 2012;Westphal et al 2013;Kim et al 2014;Prokopowicz et al 2015;Bugarski et al 2016). However, there is little information on whether using HDRD instead of ULSD in marine vessels would improve or exacerbate health effects in and near port areas.…”
Section: Introductionmentioning
confidence: 99%